The Peruvian Society of Obstetrics and Gynecology and its leadership in the promotion of women's health - Sandoval Díaz, Íther (2023)
The Peruvian Society of Obstetrics and Gynecology (SPOG, for its acronymin English) was founded on June 30, 1947, by Dr. Constantino JoséCarvallo Alzamora. In its 76 years of fruitful existence, it is an organizationrecognized for its important contributions to the quality and humanisticcare of Peruvian women's health.